(untitled) (International Journal of Nursing Education, 2020)
Globally Cancer is the second leading cause of death and approximately 9.6 million deaths due to cancerin 2018. Approximately about 1 in 6 deaths is due to cancer globally. In low and middle-income countriesapproximately 70% of deaths are due to cancer. Some common cancers in Indian women are Breast, Cervix,Ovary, Mouth & Esophagus, Colorectal and other cancers. Breast cancer is the commonest cancer amongwomen across the World as well as in India. Although rapid advancement, mammography & screening hasincreased rate of survival but women who survive continue to face medical, physical, social and psychosocialchallenges. Evaluation of quality of life is also important for understanding the effect of treatment and howmuch different factors affect quality of life of the breast cancer patients.This paper aims to predict Quality of Life (QoL) in breast cancer patients using various physical,psychological, social and spiritual domains. This descriptive and cross sectional study was undertaken todetermine the factors affecting quality of life (QOL) in breast cancer patients. Patient’s response and hospitalrecords analyses the dimensions which affects quality of life among breast cancer patients in the state ofUttar Pradesh. Findings suggest strong relationship between clinical and socio-demographical factors andbreast cancer patients’ QoL. This study demonstrates the strength of the relationship between educationand physical well-being, education with social well-being and education with spiritual well-being. A strongrelationship was found between marital status and spiritual well being. A strong relationship was foundbetween clinical stage and spiritual well being. A good relationship was found between tumor stage andsocial and spiritual well being. A strong relationship was also found between type of treatment and physical,psychological and social well being. This study fills a gap in the literature related to QoL in Indian womensuffering from carcinoma breast.